The VA National TeleNeurology Program implementation: a mixed-methods evaluation guided by RE-AIM framework - Damush, Teresa M.; Wilkinson, Jayne R.; Martin, Holly; Miech, Edward J.; Tang, Qing; Taylor, Stanley; Daggy, Joanne K.; Bastin, Grace; Islam, Robin; Myers, Laura J.; Penney, Lauren S.; Narechania, Aditi; et al. (Frontiers in Health Services, 2023)
Introduction The Veteran Affairs (VA) Office of Rural Health (ORH) funded the Veterans Health Administration (VHA) National TeleNeurology Program (NTNP) as an Enterprise-Wide Initiative (EWI). NTNP is an innovative healthcare delivery model designed to fill the patient access gap for outpatient neurological care especially for Veterans residing in rural communities. The specific aim was to apply the RE-AIM framework in a pragmatic evaluation of NTNP services. Materials and methods We conducted a prospective implementation evaluation. Guided by the pragmatic application of the RE-AIM framework, we conceptualized a mixed-methods evaluation for key metrics: (1) reach into the Veteran patient population assessed as total NTNP new patient consult volume and total NTNP clinical encounters (new and return); (2) effectiveness through configurational analysis of conditions leading to high Veteran satisfaction and referring providers perceived effectiveness; (3) adoption and implementation by VA sites through site staff and NTNP interviews; (4) implementation success through perceived management, implementation barriers, facilitators, and adaptations and through rapid qualitative analysis of multiple stakeholders’ assessments; and (5) maintenance of NTNP through monitoring quarterly TeleNeurology consultation volume. Results NTNP was successfully implemented in 13 VA Medical Centers over 2 years. The total NTNP new patient consult volume in fiscal year 2021 (FY21) was 836 (58% rurally residing); this increased to 1,706 in fiscal year 2022 (FY22) (55% rurally residing). Total (new and follow-up) NTNP clinical encounters were 1,306 in FY21 and 3,730 in FY22. Overall, the sites reported positive experiences with program implementation and perceived that the program was serving Veterans with little access to neurological care. Veterans also reported high satisfaction with the NTNP program. We identified the patient level of perceived excellent teleneurologist–patient communications, reduced need to drive to get care, and that NTNP provided care that the Veteran otherwise could not access as key factors related to high Veteran satisfaction. Conclusions The VA NTNP demonstrated substantial reach, adoption, effectiveness, implementation success, and maintenance over the first 2 years of the program. The NTNP was highly acceptable to both the clinical providers making the referrals and the Veterans receiving the referred video care. The pragmatic application of the RE-AIM framework to guide implementation evaluations is appropriate, comprehensive, and recommended for future applications.